The Routledge companion to international hospitality management - Gardini, Marco A., 1964-; Ottenbacher, Michael C., 1966-; Schuckert, Markus (New York : Routledge, 2021)
"The hospitality sector is facing increasing competition and complexity over recent decades on its development towards a global industry. The strategic response to this is still that hospitality companies try to grow outside their traditional territories and domestic markets, while the expansion patterns and M&A activities of international hotel and restaurant chains reflect this phenomenon. Interestingly, the strategies, concepts and methods of internationalization as well as the managerial and organizational challenges and impacts of globalizing the hospitality business are yet under-researched in the field of hospitality. While the mainstream research on international management offers an abundance of information and knowledge on topics, players, trends, concepts, frameworks or, methodologies, its ability to produce viable insights for the hospitality industry is limited, as the mainstream of research is taking place outside of the service sector. Specific research directions and related cases like the international dimensions of strategy, organization, marketing, sales, staffing, control, culture and others to the hospitality industry, are rarely identifiable so far. The core rationale of this book is therefore to present newest insights from research and industry in the field of international hospitality, drawing together recent scientific knowledge and state-of-the-art expertise to suggest directions for future work. It is designed to raise awareness on the international factors influencing the strategy and performance of hospitality organizations, while analyzing and discussing the present and future challenges for hospitality firms going or being international. This book will provide a comprehensive overview and deeper understanding of trends and issues to researchers, practitioners and students by showing how to master current and future challenges when entering and competing in the global hospitality industry"--
OCLC-licensed vendor bibliographic record.
Keywords: Hospitality industry -- Management